Dermoscopic and Immunohistochemical Observations in Anetodermic Pilomatricoma: A Case Report - Hao-Song Chen; Fang-Gu Li; Tian Wang; Wen-Bin Huang; Yi-Ming Fan (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)